The Psychometric Properties of an Intrinsic Motivation Scale in Conducting Research: The Application of Rasch Measurement Model - Badrasawi, Kamal J I; Idrus, Faizah; Abd Razak Al-Hafiz, Afareez; Ismail, Nik Ahmad Hisham (Academic Research Publishing Group, 2018)
Research culture a system that posits importance to conducting and communicating scholarly research, is highly expected from academic staff in the higher learning institutions. Skillful academics with high levels of (intrinsic) motivation in conducting research are most likely needed to achieve the desired research culture. Therefore, a research project has been conducted to examine the possibility of understanding and promoting research culture at a public university in Malaysia. Distinctive instruments were developed to achieve the purpose. This paper, thus, is aimed at examining the psychometric properties of a 44-item survey instrument developed to delve into the academic staff’s intrinsic motivation in conducting research. The survey was administered to 326 academic staff from various faculties in a public university. The Rasch Measurement model, which provides evidences on the fundamental measurement requirements of research instrument, was used to analyse the psychometric properties of the survey instrument using the Winsteps software program. The results of the Rasch analysis combined with qualitative investigation showed that the survey measured two distinct subscales or sub-dimensions of intrinsic motivation (namely positive and negative), which should be carried out separately in the final analysis. The resulted two subscales met the measurement requirements as evidenced by the individual analyses of the Rasch Model. Three misfit items were deleted from the first subscale (i.e. positive). Further items could be added to the two subscales to target the respondents with high ability measures. Recommendations were also given to revise the 5-point Likert scale used in the surveys in other related studies.